Reliability of the data on tuna catches obtained from the dockside in Indonesia: A study of stakeholders' perceptions. (December 2020) - Khan, Alexander M.A.; Mill, Aileen C.; Gray, Tim S.; Jiang, Mingguo; Arief, Hazmi; Brown, Arthur; Karman, Amirul; Polunin, Nicholas V.C.
Abstract: This paper is a study of stakeholders' perceptions of the reliability of landings data obtained by governments on fish stocks. The case studied is the tuna fishery in Indonesia, which is the country's most important fisheries sector in terms of income and employment, but poses particular difficulties for landings data collection because Indonesia is an archipelago made up of 17, 500 islands making data collection a very complex, time-consuming, and costly process because of the large number of ports and the need to employ a considerable team of enumerators to collect the data. This study is not an enquiry into whether the officially recorded data are reliable, but whether fishers and other stakeholders believe them to be reliable. We carried out a survey of 921 respondents (724 tuna fishers; 154 live-bait fishers; 16 policy makers; 16 public sectors and 11 private sectors) to investigate their perceptions of the way landings data on tuna are obtained and collated by Indonesian government officials. The results indicate there is considerable scepticism about the accuracy of these fisheries data. Respondents said there was inadequate funding for data collection; the enumerators were poorly trained; and there were few incentives for checking the results of surveys. These and other criticisms raise serious doubts about the efficacy of the management of the tuna fisheries in Indonesia. Stakeholders' perceptions on how to improve their confidence in the data collected include greater involvement of individual fishers and the private sector.